Legal Legitimacy of Fiscal Discretion in State Fund Placement Policy - Dhara Syera Fatria; Parluhutan Sagala; Pujo Widodo; Arief Fahmi Lubis (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Indonesia’s fiscal management framework grants the government authority to implement policies that sustain national economic stability within the bounds of legality and accountability. One such policy is the 2025 State Placement Program, established through the Minister of Finance Decree No. 276 of 2025, which allocates IDR 200 trillion of public funds to state-owned banks to enhance liquidity and support growth.  This study addresses the legal ambiguity surrounding this policy and aims to assess whether such discretion is legally and administratively legitimate within Indonesia’s fiscal governance framework. Using a normative-juridical method, the research analyzes its legal basis, mechanisms of accountability, and institutional coordination, particularly regarding the management of the Accumulated Budget Surplus (SAL) and the authority of the State General Treasurer (BUN). The findings show that fiscal discretion in this policy is legally justified when exercised according to statutory mandates and subject to transparent reporting under the State Revenue and Expenditure Budget Law (APBN). However, its implementation requires clear coordination within the Financial System Stability Committee (KSSK). The study concludes that the decree is a valid exercise of fiscal authority but necessitates stronger safeguards linking SAL and the APBN, reinforced institutional coordination, and risk-based monitoring to ensure compliance with the rule of law. The implications of this study highlight the importance of aligning discretionary fiscal actions with constitutional oversight mechanisms to preserve legality and public accountability in Indonesia’s financial administration.